2022
DOI: 10.1155/2022/1531570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Content on Mechanical Properties and Microstructural Characteristics of Alkali Resistant Glass Fiber Reinforced Concrete

Abstract: Owing to its enhanced strength, ductility, and resistance to harsh environments, increasing research attention has been paid to alkali-resistant glass fiber reinforced concrete (ARGFRC). This paper presents experimental studies concerning the effects of fiber content on the mechanical properties and microstructural characteristics of ARGFRC. The amount of glass fiber was considered at levels of 0.0, 0.3, 0.5, 0.8, 1.0, 1.3, and 1.5% of the concrete volume. The compression, flexural, impact resistance, scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…High-strength concrete has a high usage rate in high-rise buildings and bridge engineering, 30 and existing research [31][32][33] has confirmed the improvement effect of PP fiber on the mechanical properties of high-strength concrete. There is relatively little research on experimental beams, so the concrete design of this experimental beam is C55 strength grade.…”
Section: Materials Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…High-strength concrete has a high usage rate in high-rise buildings and bridge engineering, 30 and existing research [31][32][33] has confirmed the improvement effect of PP fiber on the mechanical properties of high-strength concrete. There is relatively little research on experimental beams, so the concrete design of this experimental beam is C55 strength grade.…”
Section: Materials Propertiesmentioning
confidence: 89%
“…Table 1 presents the mix proportions for PP-FRC, and Table 2 shows the basic mechanical properties of PP fibers. Many scholars [32][33][34][35][36][37][38] have studied the variation of PP-FRC flexural strength and tensile strength with fiber volume fraction and obtained different results as shown in Figure 1. When the fiber volume fraction is appropriate (0.18%-0.45%), PP fibers have a significant improvement effect on the crack resistance of concrete.…”
Section: Materials Propertiesmentioning
confidence: 99%